Effectiveness of Digital Platforms in Improving Students' Writing Skills in Higher Education: Literature Review - Nurfidah, Nurfidah; Fandir, A (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
Higher education is currently facing demands to integrate digital technology to improve the effectiveness of teaching and learning. The use of technology in education has been proven to increase access to information, learning flexibility, and innovation in teaching methods. This study aims to review the literature regarding the effectiveness of digital platforms in improving students' writing skills. The methods used include qualitative and quantitative approaches through literature reviews from trusted academic sources in the last 6 years. Research findings show that digital platforms such as Google Classroom, Moodle, Microsoft Teams, and collaborative applications such as Google Docs increase learning motivation, and interaction between educators and students, and facilitate inclusive and adaptive learning. In addition, digital feedback and collaboration in learning to write have also proven to be important. Qualitative analysis shows that the use of digital platforms has a positive impact on students' writing skills, including increasing productivity, writing quality, and active participation in learning. Based on these findings, the research emphasizes the importance of educational strategies and policies that support the comprehensive integration of digital technology to achieve more effective and efficient higher education in the future.